2018
DOI: 10.1007/s10585-018-9877-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of granulocyte macrophage colony stimulating factor (GM-CSF) in radiation-induced tumor cell migration

Abstract: Recently it has been observed in preclinical models that that radiation enhances the recruitment of circulating tumor cells to primary tumors, and results in tumor regrowth after treatment. This process may have implications for clinical radiotherapy, which improves control of a number of tumor types but which, despite continued dose escalation and aggressive fractionation, is unable to fully prevent local recurrences. By irradiating a single tumor within an animal bearing multiple lesions, we observed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Even though some studies have found that radiation induced stimulation of cytokine granulocyte-macrophage colony-stimulating factor [29,30], all these studies have been tested with large fields as are used in conventional radiation therapy. However, SBTR is a technique which allows the delivery of high doses in small fields, so it is unclear whether radiation delivered by SBRT can produce an increase of granulocyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have found that radiation induced stimulation of cytokine granulocyte-macrophage colony-stimulating factor [29,30], all these studies have been tested with large fields as are used in conventional radiation therapy. However, SBTR is a technique which allows the delivery of high doses in small fields, so it is unclear whether radiation delivered by SBRT can produce an increase of granulocyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, in livers from mice that were treated with Cabozantinib with and without irradiation, this type of cells was reduced in prevalence or entirely absent, in line with the capability of Cabozantinib to antagonize MDSC as shown in other models ( 7 , 8 ). Moreover, enhanced release of GM-CSF following irradiation of 4T1 tumors was shown to attract circulating tumor cells into the tumor bed of irradiated tumors and unirradiated secondary tumor sites, contributing to tumor re-growth ( 24 ). Cabozantinib, on the other hand, resulted in a reduced tumor growth ( Figure 4 ), thus pointing to a role for GM-CSF and MDSC recruitment in our model and an explanation for the radioresistance of tumors treated with irradiation alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expression of complement, RT has been shown to increase the expression of a number of cytokines and chemokines. Aside from the previously mentioned type I interferons, RT has been shown to induce immune cells within the tumor including TAMs and CD8+ T cells and NK cells and others to produce inflammatory cytokines including tumor necrosis factor alpha (TNF-α) (70), interleukin-1 (71), interleukin-6 (72, 73), interferon-gamma (IFN-γ) (3, 74), macrophage colony stimulating factor 1 (CSF-1, M-CSF) (75), and granulocyte macrophage colony stimulating factor (GM-CSF) (76, 77). These cytokines are critical for establishing inflammation at the irradiated site as well as induction of a cytotoxic CD8+ T cell response.…”
Section: Radiation Therapy and Innate Immunitymentioning
confidence: 99%